Cerebral blood flow and intracranial pulsatility in cerebral small vessel disease - Shi, Yulu (The University of Edinburgh, 2018)
Cerebral small vessel disease (SVD) is associated with increased risks of stroke and dementia, however the mechanisms remain unclear. Low cerebral blood flow (CBF) has long been suggested and accepted, but clinical evidence is conflicting. On the other hand, growing evidence suggests that increased intracranial pulsatility due to vascular stiffening might be an alternative mechanism. Pulse-gated phase-contrast MRI is an imaging technique that allows measuring of CBF contemporaneously with pulsatility in multiple vessels and cerebrospinal fluid (CSF) spaces. The overall aim of this thesis was to provide an overview of existing clinical evidence on both hypotheses, to test the reproducibility of CBF and pulsatility measures in phase-contrast MRI, and to explore the relationship between CBF and intracranial pulsatility and SVD features in a group of patients with minor stroke and SVD changes on brain imaging. I first systematically reviewed and meta-analysed clinical studies that have assessed CBF or intracranial pulsatility in SVD patients. There were 38 studies (n=4006) on CBF and 27 (n=3356) on intracranial pulsatility. Most were cross-sectional, and longitudinal studies were scarce. There were large heterogeneities in patient characteristics and indices used particularly for measuring and calculating pulsatility. Methods to reduce bias such as blinding and the expertise of structural image readers were generally poorly reported, and many studies did not account for the impact of confounding factors (e.g. age, vascular risk factors and disease severity) on CBF or pulsatility. Evidence for falling CBF predating SVD was not supported by longitudinal studies; high pulsatility in one large artery such as internal carotid arteries (ICA) or middle cerebral arteries might be related to SVD, but studies that measured arteries, veins and CSF in the same patients were very limited and the reliability of some pulsatility measures, especially in CSF, needs to be tested. In order to test the reproducibility of the CBF and intracranial pulsatility measures, I repeated 2D phase-contrast MRI scans of vessels and CSF on healthy volunteers during two visits. I also compared the ICA pulsatility index derived from the MRI flow waveform to that from the Doppler ultrasound velocity waveform in patients with minor stroke and SVD features. In 10 heathy volunteers (age 35.2±9.78 years), the reproducibility of CBF and vascular pulsatility indices was good, with within-subject coefficients of variability (CV) less than 10%; whereas CSF flow and pulsatility measures were generally less reproducible (CV>20%). In 56 patients (age 67.8±8.27 years), the ICA pulsatility indices in Doppler ultrasound and MRI were acceptably well-correlated (r=0.5, p<0.001) considering the differences in the two techniques. We carried out a cross-sectional study aiming to recruit 60 patients with minor stroke and SVD features. We measured CBF and intracranial pulsatility using phase-contrast MRI, as well as aortic augmentation index (AIx) using a SphygmoCor device. I first investigated the relationship between intracranial measures, and systemic blood pressure or aortic AIx, and then focused on how the intracranial haemodynamic measures related to two main SVD features (white matter hyperintensities (WMH) and perivascular spaces (PVS)). We obtained usable data from 56/60 patients (age 67.8±8.27 years), reflecting a range of SVD burdens. After the adjustment for age, gender, and history of hypertension, higher pulsatility in the venous sinuses was associated with lower diastolic blood pressure and lower mean arterial pressure (e.g. diastolic blood pressure on straight sinus pulsatility index (PI): β=-0.005, P=0.029), but not with aortic AIx. Higher aortic AIx was associated with low ICA PI (β=-0.011, P=0.040). Increased pulsatility in the venous sinuses, not low CBF, was associated with greater WMH volume (e.g. superior sagittal sinus PI: β=1.29, P=0.005) and more basal ganglia PVS (e.g. odds ratio=1.379 per 0.1 increase in superior sagittal sinus PI) after the adjustment for age, gender and blood pressure. The thesis is the first to summarise the literature on CBF and intracranial pulsatility in SVD patients, addressed the major limitations of current clinical studies of SVD, and also assessed CBF and intracranial pulsatility contemporaneously in well-characterised patients with SVD features. The overall results of the thesis challenge the traditional hypothesis of the cause and effect between low CBF and SVD, and suggest that increased cerebrovascular pulsatility, which might be due to intrinsic cerebral small vessel pathologies rather than just aortic stiffness, is important for SVD. More importantly, this pilot study also provides a reliable methodology for measuring intracranial pulsatility using phase-contrast MRI for future longitudinal or larger multicentre studies, and shows that intracranial pulsatility could be used as a secondary outcome in clinical trials of SVD. However, future research is required to elucidate the implication of venous pulsatility and to fully explore the passage of pulse wave transmission in the brain. Overall, this thesis advances knowledge and suggest potential targets for future SVD studies in terms of mechanisms, prevention and treatment.
Keywords: small vessel disease; brain imaging; white matter hyperintensities; perivascular space; pulsatility; cerebral blood flow